Effect Of Egg Weight On Hatchability And Hatching Weight Of Quail (Cortunix cortunix Japonica) - Zurina, Rita; Malianti, Lezita; Definiati, Neli; Rita, Wismalinda; Suliasih, Suliasih (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
The research was conducted to determine the fertility, hatchability and hatching weight of quail (Corturnix-corturnix japonica) eggs in various egg weights. The research was carried out experimentally using a Randomized Block Design (RAK) consisting of 3 treatments and 4 replications. This research will be carried out from October to December 2020 at Kandang Puyuh, Kasih Ibu Orphanage, Jalan Bali, Bengkulu City. The tools used in this research were 4 manual hatching machines, box-shaped with a capacity of around 300 quail eggs, scales and an electrical energy source. The materials used are 300 quail eggs and disinfectant. The research was carried out experimentally using a Randomized Block Design (CRD) with 3 treatments and 4 replications. The treatment applied is egg weight consisting of: B1 = Light (≤9.5g), B2 = Medium (9.6 – 10.5g), B3 = Heavy (≥10.6g)